2020
DOI: 10.1080/21645515.2020.1744367
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccine hesitancy among parents in Italy: a cross-sectional study

Abstract: This cross-sectional survey determined the vaccine hesitancy related to Human papillomavirus (HPV) and the determinants among parents of adolescents aged 12 and 13 years in Italy. Data was collected through a self-administered questionnaire. Two-thirds of the parents (66.7%) had heard of HPV infection and knew that the vaccination was a preventive measure. Parents who had vaccinated their child against the HPV were more likely to have this knowledge. The vast majority (88%) considered the immunization useful f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 36 publications
6
27
1
Order By: Relevance
“…While an overwhelming concern in terms of perceived vaccine safety and efficacy was dominant in this survey for the parents for refusing the HPV vaccination for their sons, parents indicated also the lack of knowledge of the infection, and because they did not feel that their sons were at risk. These findings were also consistent with the results from similar previously studies [ 14 , 15 , 16 , 17 , 18 , 19 ]. The poor GPs and parents’ knowledge and attitudes on the important role of the vaccination will prevent them from being proactive respectively in recommending and requesting vaccination services.…”
Section: Discussionsupporting
confidence: 94%
“…While an overwhelming concern in terms of perceived vaccine safety and efficacy was dominant in this survey for the parents for refusing the HPV vaccination for their sons, parents indicated also the lack of knowledge of the infection, and because they did not feel that their sons were at risk. These findings were also consistent with the results from similar previously studies [ 14 , 15 , 16 , 17 , 18 , 19 ]. The poor GPs and parents’ knowledge and attitudes on the important role of the vaccination will prevent them from being proactive respectively in recommending and requesting vaccination services.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, HCWs need to be protected from misinformation and rely only on scientific findings that are approved by health experts. This is consistent with previous studies since using media and the Internet as primary information sources has been observed to be associated with an increased likelihood for hesitancy towards vaccination among different groups of individuals compared with those influenced by a medical authority [ 35 , 36 , 37 , 38 , 39 , 40 ]. Finally, almost one-third of the participants reported that they would be seeking additional information on influenza vaccination.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with a previous study carried out in China, which found that parents with college educations or below had a higher acceptance of COVID-19 vaccines, compared with parents with master's diploma or above [36]. However, this does not agree with a study that evaluated the HPV vaccine hesitancy among parents in Italy, which found no difference between knowing that the HPV vaccine was a preventive measure for this disease and educational level [37]. This could be explained by an infodemic that occurred in LAC countries during 2020 [38,39] and could equally affect people of different educational levels.…”
Section: Discussionsupporting
confidence: 85%